2010
DOI: 10.1038/nature09264
|View full text |Cite
|
Sign up to set email alerts
|

Rb regulates fate choice and lineage commitment in vivo

Abstract: Mutation of the RB-1 tumour suppressor occurs in one third of all human tumours and is particularly associated with retinoblastoma and osteosarcoma1. Numerous functions have been ascribed to the product of the human RB-1 gene, pRB. The best known is pRB’s ability to promote cell cycle exit through inhibition of the E2F transcription factors and the transcriptional repression of genes encoding cell cycle regulators1. In addition, pRB has been shown in vitro to regulate several transcription factors that are mas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
287
2
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 294 publications
(321 citation statements)
references
References 20 publications
13
287
2
2
Order By: Relevance
“…This observation adds to a large number of studies showing that, under specific conditions, pRB can cooperate with other factors to promote the transcriptional activation of differentiation programs and regulate the expression of apoptotic regulators (for examples, see Thomas et al 2001;Ianari et al 2009;Calo et al 2010; for review, see Attardi and Sage 2013).…”
Section: The Cellular Consequences Of Rb Inactivationmentioning
confidence: 75%
See 2 more Smart Citations
“…This observation adds to a large number of studies showing that, under specific conditions, pRB can cooperate with other factors to promote the transcriptional activation of differentiation programs and regulate the expression of apoptotic regulators (for examples, see Thomas et al 2001;Ianari et al 2009;Calo et al 2010; for review, see Attardi and Sage 2013).…”
Section: The Cellular Consequences Of Rb Inactivationmentioning
confidence: 75%
“…In addition to the repression of E2F-regulated genes, pRB has been implicated in the organization of chromosomal domains and has roles in gene activation, particularly in response to apoptotic and differentiation signals (Thomas et al 2001;Ianari et al 2009;Calo et al 2010). The RNA signatures associated with RB1 mutation include both up-regulated and down-regulated transcripts (Black et al 2003;Markey et al 2007;Ertel et al 2010).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the transcriptional regulator and tumor suppressor retinoblastoma-associated protein (pRb), has been shown to be an important switch with the potential of directing mesenchymal stem cells toward either an osteoblast or adipocyte lineage. Calo et al 39 showed that pRb directs common mesenchymal precursor cells into an osteoblastic cell fate while inhibiting their differentiation into adipocytes, and that loss of pRb in these precursors greatly increased the presence of BAT at the expense of calcified bone.…”
Section: The Connection Between Bat and Bonementioning
confidence: 99%
“…This sequence is homologous to the DNA sequences capable of interaction with the tumor suppressor retinoblastoma protein (Rb) located in promoters of the multiple genes involved in both cellular proliferation (29 -34) and differentiation (35)(36)(37)(38). This observation was followed by the suggestion that such retinoblastoma control elements (RCE) would also modulate transcription of tropoelastin gene.…”
mentioning
confidence: 99%